Rigid multi-body kinematics of shovel crawler-formation interactions. Issue 4 (3rd July 2016) - Frimpong, Samuel; Thiruvengadam, Magesh
Abstract : Large capacity shovels are deployed in surface mining operations for achieving economic bulk production targets. These shovels use crawler tracks for effective terrain engagement in these environments. Shovel reliability, maintainability, availability and efficiency depend on the service life of the crawler tracks. In rugged and challenging terrains, crawler wear, tear, cracks and failure are extensive resulting in prolonged downtimes with severe economic implications. In particular, crawler shoe wear, tear, cracks and fatigue failures can be expensive in terms of maintenance costs and production losses. No fundamental research has been undertaken to understand the crawler-formation interactions in challenging and rugged terrains in surface mining operations. This study forms the foundations for providing long-term solutions to crawler failure problems. The kinematic equations governing the crawler-formation interactions have been formulated to characterise the crawler motions during shovel production. These equations capture the motions governing the link pin joint, oil sand terrain joint and driving constraints based on the multi-body rigid theory. Crawler propel is achieved by using prescribed velocities along a translational degree of freedom (DOF) and a translational and rotational DOF. The crawler kinematic solutions show that the 3-D crawler–terrain model results in 132 DOFs and requires dynamic modelling to obtain the unknown degrees of freedom. A 3-D virtual prototype model is built to capture the crawler-formation interaction in MSC ADAMS based on the rigid body crawler kinematics. The virtual prototype simulator is supplied with mass properties of crawler shoe, mass, stiffness and damping characteristics of oil sand and external loads due to machine weight and contact forces to obtain the time variation of position, velocity and acceleration for the crawler–terrain engagement for given driving constraints. The results from the driving constraints yield a non-linear longitudinal motion of the crawler track assembly. The crawler track lateral and vertical displacements during translation-only motion fluctuates with maximum magnitudes of 0.7 and 3.6 cm. Similarly the fluctuating longitudinal, lateral and vertical velocities and accelerations have maximum magnitudes of 0.22, 0.046 and 0.56 m/s and 7.41, 1.73, and 34.9 m/s 2, respectively. This research provides a strong foundation for further study on developing flexible crawler track model for predicting crawler shoes dynamic stress distributions, cracks development and propagation and fatigue analysis during shovel operations.